2008
DOI: 10.1038/jp.2008.8
|View full text |Cite
|
Sign up to set email alerts
|

Low-density lipoprotein profile changes during the neonatal period

Abstract: Objective: To investigate natural change of low-density lipoprotein (LDL) profile during the neonatal period and the impact of gestational age and birth weight on those changes.Study Design: We measured lipid composition in LDL fraction, LDL particle size and apolipoprotein B (apoB) concentration at birth, 5 days of age and 1 month of age in 63 healthy neonates that had 37 to 41-week gestational age.Result: Low-density lipoprotein cholesterol and apoB concentrations increased from birth to 5 days of age, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 23 publications
2
19
0
2
Order By: Relevance
“…This finding is consistent with clinical reports (5,23). Interestingly, the hepatic gene array data demonstrate significant upregulation of mRNAs encoding enzymes in the mevalonate pathway, important in endogenous cholesterol synthesis, in piglets fed either cow's milk or soy formulas, relative to breast-feeding.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with clinical reports (5,23). Interestingly, the hepatic gene array data demonstrate significant upregulation of mRNAs encoding enzymes in the mevalonate pathway, important in endogenous cholesterol synthesis, in piglets fed either cow's milk or soy formulas, relative to breast-feeding.…”
Section: Discussionsupporting
confidence: 91%
“…Breast milk is high in cholesterol and long chain saturated fats, while formula contains no cholesterol and substantial amounts of short chain saturated fats. Higher total and LDL-cholesterol values have been reported in breast-fed compared with cow's milk-fed infants (5,23). Moreover, increased urinary and fecal bile acid excretion has been reported in 3 mo old infants fed formula compared with those who were breast fed (30,57).…”
mentioning
confidence: 93%
“…The cord lipid profiles are similar to those in Manchester children from the hyperglycaemia and adverse pregnancy outcomes (HAPO) study [30] and to those in Ibadan about 30 years ago, but slightly lower than those reported in eastern Nigeria [17,31,32]. Cord HDL-C and TG levels are about half that of adults while TC and LDL-C are about one-third, hence HDL is the major lipid moiety [33,34]. …”
Section: Discussionsupporting
confidence: 52%
“…The characteristic distribution of TG in term neonates, especially the relatively high LDL-TG concentration, may partly be explained by a reduction in hepatic lipase activity [4]. However, lipase activity, even including lipoprotein lipase (LPL), cannot fully explain the mechanism of TG distribution because TG concentrations were markedly low.…”
Section: Discussionmentioning
confidence: 98%
“…In cord blood, low-density lipoprotein (LDL) is rich in triglycerides (TG) compared with adult blood; and in the high-density lipoprotein (HDL) fraction, apolipoprotein E-rich large particles are dominant [2][3][4]. In term neonates, gestational age appears to markedly influence the LDL profile, but not the HDL profile, in cord blood [3,4]. Very low-density lipoprotein (VLDL) is a large, TG-rich particle synthesized in the liver.…”
Section: Introductionmentioning
confidence: 99%